2019
DOI: 10.1007/s00109-019-01743-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of sirtuin-1 in diabetic nephropathy

Abstract: Diabetic nephropathy (DN) is a research priority for scientists around the world because of its high prevalence and poor prognosis. Although several mechanisms have been shown to be involved in its pathogenesis and many useful drugs have been developed, the management of DN remains challenging. Increasing amounts of evidence show that silent information regulator 2 homolog 1 (sirtuin-1), a nicotinamide adenine dinucleotide (NAD+)–dependent protein deacetylase, plays a crucial role in the pathogenesis and devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
73
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 152 publications
1
73
2
1
Order By: Relevance
“…Diet restriction intervention could improve the autophagy function of the kidney and alleviate kidney damage caused by diabetes mellitus. This process is regulated by silent mating type information regulation 2 homolog 1 (Sirtl) . Sirt1 is a NAD + dependent deacetylase and an important regulator of FOXO1 transcriptional function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diet restriction intervention could improve the autophagy function of the kidney and alleviate kidney damage caused by diabetes mellitus. This process is regulated by silent mating type information regulation 2 homolog 1 (Sirtl) . Sirt1 is a NAD + dependent deacetylase and an important regulator of FOXO1 transcriptional function.…”
Section: Introductionmentioning
confidence: 99%
“…This process is regulated by silent mating type information regulation 2 homolog 1 (Sirtl). 10 Sirt1 is a NAD + dependent deacetylase and an important regulator of FOXO1 transcriptional function. It can regulate FOXO1 through deacetylation, promote its expression and enhance its transcriptional activity.…”
mentioning
confidence: 99%
“…Although DN pathogenesis has made progress, its high incidence and poor prognosis have not been greatly improved [19]. Therefore, excavating novel therapeutic targets for DN is significant.…”
Section: Discussionmentioning
confidence: 99%
“…One previous study suggested that SIRT1 decreased activation of NLRP3 inflammasome in vitro [10]. Furthermore, SIRT1 was found to preserve podocyte function by regulating claudin-1, which induces podocyte effacement and albuminuria [46,47]. Hence, the AMPK/SIRT1 signaling pathway could be a therapeutic target in diabetic kidney damage.…”
Section: Discussionmentioning
confidence: 99%